Molecular excitons and plasmons in acenes and their radical cations - Weidlich, Anna; Dreuw, Andreas (Journal of computational chemistry, 2025)
For existing and potential applications of acenes and acene derivatives, properties of their excited states play a central role. In describing these, the molecular orbital picture can reach its limits, and consideration within the quasi-particle picture can enable further insight. In this work, exciton size (d_exc), hole and electron size (sigma_h and sigma_e) and correlation coefficient (R_eh) of excited states of acenes and acene cations are investigated using TD-DFT at the TDA/CAM-B3LYP/6-311G* level, with a focus on their development with increasing acene length. Furthermore, employing a previously established approach, it is shown that the electronic structure of the 1Bb and 2Bb states of neutral and cationic anthracene can be understood as molecular plasmons.
Online veröffentlicht: 18 August 2025
Gesehen am 15.01.2026